Effect of graphene oxide on demulsification process of heavy crude oil emulsion / Muhammad Faizal Sahak - Sahak, Muhammad Faizal (2019)
Emulsion is one of the common problem that occur in the oil and gas industry. From ages many researcher develop method like biological, chemical, electrical and mechanical way to overcome and treat the problem. Untreated emulsion can cause a lot of problem either in the production, transportation or in the refining Chemical demulsification is one of the famous method to separation of oil and water emulsion..The higher price of chemical used in the market industry create a potential study on the graphene oxide as a demulsifier. Recent study on Graphene oxide show ability to act as efficient demulsifier. The abundance and cheap price can be problem solver to the emulsion problem. The synthesis of graphene oxide created from raw graphite that undergo strong oxidation based on Hummer method. The categorization of sample can be determine by using FTIR and XRD test. FTIR used to detect common functional group especially on Graphene Oxide which is state to have an oxygen group like hydroxyl, carbonyl and alkoxyl. XRD was used as definite method to ensure the synthesis of graphene oxide was successful based on typical graphene oxide peak. The test for the efficiency study of graphene oxide as demulsifier can be divided in two part which is bottle test and Interfacial tension. The demulsification process efficiency of added graphene oxide can yield in the range of 99.87% to 99.98%. The reason can be supported by the interfacial tension reduction with increasing concentration of graphene oxide.